Krüppel-Like Factor 7 is a Marker of Aggressive Gastric Cancer and Poor Prognosis - Zhonghua Jiang; Tingting Yu; Zhining Fan; Hongmei Yang; Xin Lin (Cellular Physiology and Biochemistry, 2017)
Background/Aims: Krüppel-like factor (KLF) 7 protein is a member of the KLF transcription factor family, which plays important roles in regulating the expression of genes involved in cell growth, proliferation, differentiation and metabolism. However, the role of KLF7 in gastric cancer (GC) is unknown. The aim of this study is to explore the role of KLF7 in GC and its correlation with clinicopathological characteristics and prognosis of GC patients. Methods: We first systematically evaluated dysregulation of the KLF family in The Cancer Genome Atlas (TCGA) GC database. Then, 252 patients who underwent surgery for GC were enrolled to validate the results from the TCGA. Functional studies were also used to explore the role of KLF7 in GC. Results: In the TCGA database, we found that KLF7 was an independent predictor for survival by both univariate and multivariate analysis (P<0.05). In a validation cohort, KLF7 expression was significantly increased in GC tissues compared with adjacent normal controls (P=0.013). High KLF7 expression correlated with inferior prognostic factors, such as T stage (P=0.022), N stage (P =0.005) and lymphovascular invasion (P=0.009). Furthermore, we observed a strong negative correlation between KLF7 expression and 5-year overall survival and disease-free survival in GC patients (P<0.05). Moreover, our in vitro studies showed a notable decrease in migration in KLF7 knockdown cells. Conclusion: KLF7 has an important role in GC progression, as it inhibits GC cell migration and may serve as a prognostic marker.